(untitled) («СОВРЕМЕННЫЕ ТЕХНОЛОГИИ КОМПЬЮТЕРНОЙ ЛИНГВИСТИКИ», 2024)
In the article, it is one of the urgent issues to apply information technologies to the educational process, which is rapidly entering, using computers and information technologies to create new opportunities in the field of education, educational activities and the development of students’ creative thinking, about the child’s knowledge through computer tools, to realize moral, creative, communication and aesthetic possibilities and abilities, and for this the teacher himself should be well aware of the field of information technologies, the information of structured computer training programs should be mastered by the student it is explained that if psychological and pedagogical rules are taken into account, it allows for individualization and differentiation of teaching, stimulation of children’s interests and independent activity in learning.